ROLE OF FAMILY IN IMPLEMENTATION OF DIABETES EXERCISE IN TYPE 2 DIABETES MELITUS PATIENTS - Lono Wijayanti (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2018)
Introduction: Diabetes mellitus is a group of metabolic diseases characterized by an increase in blood glucose levels (hyperglycemia), which occurs due to abnormal insulin secretion, insulin activity and both (Brunner & Suddarth, 2014). The role of the family is needed for diabetics related to well-being and health where the family environment is a place for individuals to learn for life (Friedman, 2010). The role of the family is the most powerful indicator in giving a positive impact on the implementation of diabetes exercise which acts as a glicemic control which is controlling and regulating blood sugar levels.Objective: The aim of the study was to describe the role of families in implementing diabetes exercise in type 2 Diabetes Mellitus (DM) patients at Gayungan Health Center, Dukuh Menanggal, Surabaya.Method: The design of this study used descriptive research. The population is all families who have family members with diabetes mellitus cases with a large sample of 4O people. Sampling using the Total sampling technique The variables studied were the role of family in implementing diabetes exercise. Data collection is done by distributing questionnaires.Results: The results of the study showed that of the 40 respondents in the Gayungan Community Health Center working area in Dukuh Menanggal dated 40% the role of good family, 32.5% was sufficient, 27.5 was lacking in supporting the implementation of diabetes exerciseConclusion: The family role of almost half is in the good category. The family should play an active role in the management of diabetes exercises in family members who suffer from diabetes mellitus so that blood glucose levels can be controlled properly. Keywords: The role of the family, diabetes exercise, diabetes mellitus.